The Effect of Financial Performance on Stock Returns in Consumer Goods Sector Companies Listed on The Indonesia Stock Exchange for the 2016-2021 Period - Valeriani Pau Tuni Lasa; Matrodji H.Mustafa (International Journal of Social Service and Research, 2023)
This research aims to analyze and examine the factors that influence the stock return of the consumer goods sector listed on the Indonesia Stock Exchange. The research data is annual data for the observation period from 2016 to 2021 obtained from the company's annual report. The sampling method used was purposive sampling. From 57 companies as a population, 15 companies were taken as samples. Then based on the Chow test and Hausman test, the data analysis method used in this study is panel data regression with Fixed Effect Mode. The results of the study have shown that Return on Assets has a positive effect on stock returns, Debt to Assets ratio has a negative effect on stock returns, while current ratio, Total Asset turnover, and Size have no effect on stock returns